Analysis of challenges in the application of deterministic wireless channel modelling in the implementation of WLAN–based indoor location system in large complex scenarios. (20th March 2014) - Sesma, Iris; Azpilicueta, Leire; Astrain, José Javier; Villadangos, Jesús; Falcone, Francisco
This paper describes user location and tracking on indoor scenarios based on the pattern recognition of IEEE 802.11 signal strength measurements by means of a fuzzy inference system. Signal fluctuation makes difficult and imprecise the trilateration of the user location, so we propose the use of fuzzy techniques to deal with such imprecision. To implement the location system, deterministic wireless channel characterisation is obtained by means of in–house implemented 3D ray launching code. Several scenarios are analysed, since their size strongly impacts on algorithm convergence. The limitations and solution, based on subdivision of the scenario in sub–zones, are analysed and applied to the case of a new emergency hospital complex in Navarra. Simulation and measurement results are presented showing good agreement. The results can aid in the determination of an optimised WiFi–based location system providing efficient positioning and communication services in complex indoor scenarios.